2001
DOI: 10.1091/mbc.12.11.3417
|View full text |Cite
|
Sign up to set email alerts
|

Lag1p and Lac1p Are Essential for the Acyl-CoA–dependent Ceramide Synthase Reaction inSaccharomyces cerevisae

Abstract: Lag1p and Lac1p are two homologous transmembrane proteins of the endoplasmic reticulum in Saccharomyces cerevisiae. Homologous genes have been found in a wide variety of eukaryotes. In yeast, both genes, LAC1 and LAG1, are required for efficient endoplasmic reticulum-to-Golgi transport of glycosylphosphatidylinositol-anchored proteins. In this study, we show that lag1⌬lac1⌬ cells have reduced sphingolipid levels due to a block of the fumonisin B1-sensitive and acyl-CoA-dependent ceramide synthase reaction. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
271
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 264 publications
(279 citation statements)
references
References 39 publications
(38 reference statements)
7
271
0
1
Order By: Relevance
“…47 And lastly, but most importantly, convincing evidence for ceramide's involvement in the process of aging comes from studies in yeast, where the longevity assurance genes, LAG1 and LAC1, in yeast that participate in de novo ceramide biosynthesis, have been shown to determine yeast lifespan. 48 In summary, we present evidence that NSMase-2 plays a crucial role in the regulation of hepatic functions during aging and mediates aging-associated hyperresponsiveness to IL-1␤ (Fig. 7).…”
Section: Discussionmentioning
confidence: 58%
“…47 And lastly, but most importantly, convincing evidence for ceramide's involvement in the process of aging comes from studies in yeast, where the longevity assurance genes, LAG1 and LAC1, in yeast that participate in de novo ceramide biosynthesis, have been shown to determine yeast lifespan. 48 In summary, we present evidence that NSMase-2 plays a crucial role in the regulation of hepatic functions during aging and mediates aging-associated hyperresponsiveness to IL-1␤ (Fig. 7).…”
Section: Discussionmentioning
confidence: 58%
“…Conversely, an excess of sphingolipids is also toxic, leading to ER stress and disruption of calcium homeostasis (LloydEvans et al 2008;Han et al 2010). Increased levels of ceramides or LCB-Ps cause lethality in yeast (Schorling et al 2001;Zhang et al 2001), and a number of human lysosomal storage diseases, including Tay-Sachs disease, Niemann-Pick disease, and Gaucher disease, are attributable to mutations that block sphingolipid breakdown (Schulze and Sandhoff 2011). Additionally, a heredity sensory neuropathy has recently been shown to be caused by accumulation of nondegradable sphingolipid metabolites (Gable et al 2010;Penno et al 2010).…”
Section: Mechanisms Of Sphingolipid Homeostasismentioning
confidence: 99%
“…It has been shown previously that endogenous ceramide can be generated by various mechanisms, including de novo synthesis of ceramide, or activation of sphingomyelinases (11 -13). One of the key enzymes of the de novo pathway is (dihydro)ceramide synthase, and it has been shown that in Saccharomyces cerevisiae, longevity assurance gene (LAG) members (LAG1p and Lac1p) play a role in the regulation of life span (14) and are also required for ceramide synthase activity (15,16). Recent studies also revealed that one of the mouse homologues of these proteins, known as upstream of growth and differentiation factor 1 (mUOG1 or mouse LASS1) specifically regulates the synthesis of stearoyl (C 18 )-containing sphingolipids, including C 18 -ceramide (17,18).…”
Section: Introductionmentioning
confidence: 99%